The Influence of Collaborative Model between the Role of Husbands and Healthcare Workers on Mother’s Behavior in Giving Exclusive Breastfeeding - Stang, Stang; Abdullah, Tahir; Marwang, Sumarni (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Considering the importance of giving exclusive breast milk (ASI) for the growth and development of children, collaborative support between health workers and husbands is very important. Support from husbands allows mothers to carry out breastfeeding process easier, so that the mothers’ mental condition will be stable and not stressful, and they will not feel exhausted. As a result, the mothers can provide the best breast milk. AIM: The aim of this study is to analyze the influence of a collaborative model on the role of husbands and health workers to improve mother’s behavior in giving exclusive breastfeeding. METHODS: This research used a quasi-experimental design. The intervention group consisted of husbands of third-trimester pregnant women who came from the working area of the Mangkoso Community Health Center, while the control consisted of husband from the Padongko Community Health Center, each group consisted of 30 people. In the intervention group, the collaborative model between the roles of husbands and health workers was applied, while in the control group, the husbands only received Maternal and Child Handbook (KIA). RESULT: The results showed that there were differences in knowledge about the role of husbands in supporting the exclusive breastfeeding between the intervention group and the control group with a value of p = 0.000. Knowledge of the husband’s role in supporting exclusive breastfeeding in the intervention group was very good, but it was bad in the control group. In the other hand, there was no differences in behavior of giving exclusive breast milk (ASI) between the intervention group and the control group with a value of p = 0.422. CONCLUSION: However, if we compared the behavior of exclusive breastfeeding before and after the application of the model in the intervention group, the increase was found to be very significant, which was 57.5%, from 12.5% to 70%. While in the control group the increase was only 20.9%, from 35.8% to 56.7%.